How can Entrustable Professional Activities serve the quality of health care provision through licensing and certification? - ten Cate, Olle (Canadian Medical Education Journal, 2022)
This paper about Entrustable Professional Activities (EPAs) was solicited to support the discussion about the future of licensing within the Medical Council of Canada. EPAs, units of professional practice to be entrusted to learners or professionals once they have shown to possess sufficient competence, were proposed in 2005 to operationalize competency-based postgraduate medical education and have become widely popular for various health professions education programs in many countries. EPAs break the breadth of competence for license down to units of practice that can be overseen, assessed, monitored, documented, and entrusted. EPAs together may constitute an individual's portfolio of qualifications, and define a scope of practice. A medical license and a specialty certification can then be defined as the required combination of EPAs for which one is qualified at any specific moment in time. That 'snapshot' could change over time and reflect the professional development of the individual, both in their competence and in their privileges to practice. Micro-credentialing and digital badges might become an adequate option to show-case one's scope of practice at any time and operationalize the idea of a dynamic portfolio of EPAs.